2022
DOI: 10.22336/rjo.2022.48
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and musculoskeletal changes in the pediatric population using gadgets

Abstract: Objective. Analysis of ophthalmological and musculoskeletal changes secondary to the use of electronic devices with digital screen, such as smartphones, laptops, computers or tablets. Material and Methods. This paper represents is a prospective observational study of 35 participants with ages between 6 and 17. The ophthalmological exam was carried out for all participants in the Ophthalmological Clinic of “Sf. Spiridon” Emergency Hospital, Iaşi, and the exam of musculoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…58,59 Computer Vision Syndrome (CVS) which represents a group of visual and extraocular symptoms associated with sustained use of visual display terminals was shown to result in asthenopia, blurred vision, dry eye syndrome, and ocular congestion as the most frequent manifestations of VI. [60][61][62] The result of this study not being able to establish significant relationship between the variables may be due to the small sample size used, which is major limitation to this study.…”
Section: Discussionmentioning
confidence: 90%
“…58,59 Computer Vision Syndrome (CVS) which represents a group of visual and extraocular symptoms associated with sustained use of visual display terminals was shown to result in asthenopia, blurred vision, dry eye syndrome, and ocular congestion as the most frequent manifestations of VI. [60][61][62] The result of this study not being able to establish significant relationship between the variables may be due to the small sample size used, which is major limitation to this study.…”
Section: Discussionmentioning
confidence: 90%
“…A study conducted in 2022 analyzed the ocular and musculoskeletal modifications determined by the use of digital screens in children. The research found that musculoskeletal symptoms were encountered in large numbers in all participants, which suggests that musculoskeletal changes should be analyzed and treated very seriously in CVS [ 67 ].…”
Section: Extraocular Symptomsmentioning
confidence: 99%
“… 44 Electronic devices might be responsible for accommodative disorders and convergence insufficiency in pediatric users. 47 There is lack of studies in the literature investigating the macular integrity and functions. 25 …”
Section: Introductionmentioning
confidence: 99%
“…9,22,29,31,34,36 Several studies concluded that the unexplained reduction in the visual functions and performances could be attributed to the smartphones and digital screens. 7,8,10,13,[39][40][41][42][43][44][45][46][47] Electronic devices or screens might be responsible for the emergence of unexplained recent era of deterioration of visual functions and performances with underlying mechanisms not fully understood. 13 Reduction of the visual sensitivity in the dark with smartphone use has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation